1997
DOI: 10.1007/bf02778134
|View full text |Cite
|
Sign up to set email alerts
|

Is signal transduction modulated by an interaction between heterotrimeric G-proteins and tubulin?

Abstract: Although it is generally accepted that tubulin plays an important role in G-protein-mediated signal transduction in a variety of systems, the mechanism of this phenomenon is not completely understood. G-protein-tubulin interaction at the cell membrane and the cytosol, and the influence of such an interaction on cellular signaling are discussed in this review article. Because the diameter of a microtubule is 25 nm and the plasma membrane is 9-11 nm thick, it is not possible for membrane-associated tubulin to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 217 publications
0
12
0
Order By: Relevance
“…Second, the presence of lipid-anchored tubulin within DRF could play a role in signal transduction. In fact, domains are enriched in signal-transducing molecules, G-protein families included (10 -12), and it is known that tubulin is involved in G-protein-mediated signal transduction in a variety of systems (61). The interaction between these two protein families inside domains can affect signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the presence of lipid-anchored tubulin within DRF could play a role in signal transduction. In fact, domains are enriched in signal-transducing molecules, G-protein families included (10 -12), and it is known that tubulin is involved in G-protein-mediated signal transduction in a variety of systems (61). The interaction between these two protein families inside domains can affect signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported a similar distribution of detyrosinated α-tubulin in a range of cell types (Wheatley et al 1994 ;Poole et al 1997), although the significance of the punctate staining near the cell membrane is not known. Tubulin heterodimers are thought to function in the membrane environment as polymers arranged into short protofilaments (Ravindra, 1997), and if true of chondrocytes, could explain this cortical punctate staining. ID5 is located within the most stable subset of cytoplasmic microtubules (Geuens et al 1986 ;Skoufias et al 1990 ;Thyberg & Moskalewski, 1993), the differentiation and stability of these structures reflecting their importance to the integrity and function of the microtubular cytoskeleton.…”
Section: The Differential Cytoplasmic Distribution Of α-Tubulin Isoformsmentioning
confidence: 99%
“…Matrix macromolecules form transmembrane linkages with acetylated and detyrosinated ciliary microtubules, which are structurally linked to the diplosomal centrioles and determine the position of the centrosome and MTOC within the cytoplasm. Microtubules are known to participate in cellular signalling by communicating physical changes in microtubular conformation from one locus in the cell to other regions of the cytoplasm (Ravindra, 1997). It is therefore possible that the primary cilium could ' sense ' the biomechanical and\or physicochemical properties of the matrix and transduce this information into a cellular response mediated via the microtubular cytoskeleton.…”
Section: Primary Cilia -A Cybernetic Probe For Chondrocytes?mentioning
confidence: 99%
“…In a set of experiments on transfected HEK-293 cells, we were able to demonstrate that prolonged treatment with thyrotropin-releasing hormone induced not only downregulation of total cellular G q a/G 11 a but caused a dramatic shift of these proteins from plasma membranes to the high-speed supernatant [48,49,73]. The appearance of G q a/G 11 a in the cytosol fraction of GH3 and AtT-20 cells was reported by Ravindra [74]. Arthur and coworkers [75] have shown that even short-term treatment of MDCK cells with bradykinin leads to translocation of a significant portion of G q a/G 11 a from plasma membranes to the cytosol.…”
Section: Hormone-induced Solubilization Of G Protein a A Subunitsmentioning
confidence: 58%